Noninvasive Near-infrared Imaging of Fluorochromes within the Brains of Live Mice: An In Vivo Phantom Study - Jan Klohs; Jens Steinbrink; Till Nierhaus; Riad Bourayou; Ute Lindauer; Peyman Bahmani; Ulrich Dirnagl; Andreas Wunder (Molecular Imaging)
Near-infrared fluorescence (NIRF) imaging has great potential for studying physiological and pathophysiological processes noninvasively in several locations of the body. In this study, we evaluated the feasibility of NIRF imaging to visualize fluorescent compounds within the brains of live mice commonly used in brain research. To simulate the presence of a molecular NIRF reporter agent at the site of a lesion, we developed a new in vivo phantom model wherein capsules containing different amounts of an NIRF dye (Cy5.5) were stereotactically implanted deep into the left hemispheres of living mice. To precisely locate the implanted capsules, magnetic resonance imaging (MRI) was performed. Fluorescence reflectance imaging (FRI) and transillumination fluorescence imaging (TFI) were conducted to analyze and compare sensitivity and target-to-background ratios of the two methods. The sensitivities of FRI and TFI to background fluorescence from circulating dye was tested by imaging fluorescent capsules in mice intravenously injected with increasing amounts of long-circulating Cy5.5-dextran. The results show that capsules containing dye amounts as low as 10 −12 mol can be detected. TFI yielded significantly higher target-to-background ratios than FRI at 10 −11 mol ( p < .05). Comparatively low amounts of fluorescence in the blood vessels can extinguish the signal. We conclude that keeping the signal from circulating NIRF dye low, NIRF imaging offers high sensitivity in detecting fluorochromes noninvasively within brains of mice, especially by using TFI. This encourages the application of NIRF for molecular imaging in the mouse brain using NIRF reporters.